Hydrostatic pressure–volumetric strain relationship of steel fiber-reinforced concrete under different stress conditions. (30th October 2020) - Huang, Ruiyuan; Meng, Long; Qin, Jian
Highlights: The stress rate had no significant effect on the initial bulk modulus. The expression of hydrostatic pressure corresponding to the elastic limit is given. The damage evolution equations under different stress conditions are proposed. The equation of state of the damaged SFRC was generated. Abstract: A series of split Hopkinson pressure bar tests and triaxial compression tests were performed on steel fiber-reinforced concrete (SFRC) specimens with different fiber contents (0%, 0.75%, and 1.5%). The stress–strain curves of the SFRC under different strain rates and confining pressures were plotted, and the experimental data were expressed as a hydrostatic pressure-volumetric strain relationship using an appropriate conversion formula. The experimental results demonstrated that the stress rate had no significant effect on the initial bulk modulus, and the hydrostatic pressure-volumetric strain relationship was related to the stress condition and the damage evolution. The hydrostatic pressures at the limit of elastic deformation, which were related to the stress condition, were first determined in this study. Subsequently, damage evolution equations under different stress conditions were derived on the basis of experimental data obtained under different confining pressures. Finally, a new equation of state of the damaged SFRC was generated. The predictions results obtained on the basis of the new equation of state were in good agreement with the experimental results.